Investigation on rheological properties of water-based novel ternary hybrid nanofluids using experimental and Taguchi method - Zayan, Jalal Mohammed; Rasheed, Abdul Khaliq; John, Akbar; Khalid, Mohammad; Ismail, Ahmad Faris; Aabid, Abdul; Baig, Muneer (MDPI, 2021)
This study presents the rheological behavior of water-based GO-TiO2 -Ag and rGO-TiO2 -Ag ternary-hybrid nanofluids. The impact of nanoparticles’ volumetric concentration and temperature on the rheological properties were studied. All experiments were performed under temperatures ranging from 25 to 50 ◦C in the solid volume concentration range of 0.5–0.00005%. The data optimization technique was adopted using the Taguchi method. The types of nanomaterials, concentration, temperature, and shear rate were chosen to optimize the viscosity and shear stress. The effect of shear stress, angular sweep, frequency sweep, and damping factor ratio is plotted. The experimental results demonstrated that the rheological properties of the ternary hybrid nanofluid depend on the ternary hybrid nanofluid’s temperature. The viscosity of ternary hybrid nanofluids (THNf) change by 40% for GO-TiO2 -Ag and 33% for rGO-TiO2 -Ag when temperature and shear rates are increased. All the ternary hybrid nanofluids demonstrated non-Newtonian behavior at lower concentrations and higher shear stress, suggesting a potential influence of nanoparticle aggregation on the viscosity. The dynamic viscosity of ternary hybrid nanofluid increased with enhancing solid particles’ volume concentration and temperature.